The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2147/ppa.s130276
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating patient preference and satisfaction for human immunodeficiency virus therapy in France

Abstract: ObjectivesThe objectives were 1) to elicit relative preferences for attributes of antiretroviral therapies (ART) in people living with HIV (PLWH) and 2) to explore satisfaction and adherence with current ART.Patients and methodsWe conducted a multicenter cross-sectional study, consecutively enrolling PLWH receiving an ART. The quantitative part estimated the strength of preference for different attributes using an online discrete choice experiment (DCE). DCE data were analyzed using a mixed logit regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 37 publications
3
32
1
Order By: Relevance
“…Our study, using a DCE, offers the advantage to assess the trade-offs between the most important attributes. Furthermore, previous DCEs have investigated patients' preferences in HIV treatment in Europe [16][17][18] . These studies also showed that efficacy and quality-of-life are important attributes for HIV patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study, using a DCE, offers the advantage to assess the trade-offs between the most important attributes. Furthermore, previous DCEs have investigated patients' preferences in HIV treatment in Europe [16][17][18] . These studies also showed that efficacy and quality-of-life are important attributes for HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, a literature review in PubMed was conducted to examine which attributes were used in previous DCEs on patients' preferences in HIV treatment [16][17][18][19][20][21]30 . In addition, a previous best-worst scaling study of Hendriks et al 22 , which identified the most important treatment characteristics of HIV patients in Colombia, was used as the main basis for the attributes of the present study.…”
Section: Attributes and Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying assumptions in a DCE are that healthcare interventions can be described by their attributes (or characteristics) and that a respondent's valuation of an intervention depends on the level of each of these attributes . In DCE, respondents are presented with several pairs of hypothetical designs.…”
Section: Methodsmentioning
confidence: 99%
“…27 DCEs are used increasingly to understand patient perspectives and to design patient-centred interventions. Although DCEs have been used in various contexts related to HIV, including testing, 20 28-32 prevention, [33][34][35][36] service delivery, [37][38][39] and treatment, [40][41][42][43][44] to our knowledge, DCEs have not yet been used to systematically design HCT interventions.…”
Section: Introductionmentioning
confidence: 99%